Analysis of the Effect of PSAK 109 Implementation on Good Corporate Governance of Amil Zakat Institutions - Dedi Rahman; M. Koesmawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
In 2020, the Indicators of Zakat Potential Mapping (IPPZ) also released the total potential for collecting zakat funds of IDR 327.6 trillion. However, Puskas Baznas in 2021 publicized that the collection of zakat funds was only around 4% of the total potential collection. The implementation of the principles of Good Corporate Governance is an effort to optimize the collection and utilization of zakat funds by encouraging the performance of zakat management organizations to be more effective, efficient and professional. PSAK 109 on accounting for zakat infak and sedekah aims to standardize the financial governance of zakat management organizations which includes standards of recognition, measurement, presentation and disclosure. The purpose of this study is to analyze the effect of PSAK 109 implementation on strengthening the Good Corporate Governance of the Amil Zakat Institution. This research is quantitative research with an explanatory approach conducted at LAZ Al Bunyan Bogor and LAZ Sinergi Foundation Bandung. From the research results, the ttable value is 1.734 and the tcount value is 2.252. So that the tcount value of 2.252 is greater than the ttable of 1.734 (2.252> 1.734), then Ha is accepted. If Ha is accepted, it can be concluded that the application of PSAK 109 affects Good Corporate Governance at LAZ Al Bunyan and LAZ Sinergi Foundation